Platoon Diffusion along Signalized Corridors. (2016) - Praveen, P.S.; Ashalatha, R.
Abstract: Management and control of traffic flow on urban arterial streets with traffic signals at intersections actualize platoons at the exit of a given traffic signal, which do not remain intact as they progress along the arterial link and tend to disperse. The platoon characterizing variables such as platoon size, intra-platoon headway, inter-platoon headway and platoon speed has been studied extensively under homogeneous traffic conditions but such similar studies have not been conducted adequately considering the diversity of traffic and lack of lane discipline exhibited under heterogeneous traffic conditions. This study enables better understanding of platoon characterizing variables under heterogeneous traffic conditions facilitating enhanced safety and better operation. Data were collected using video graphic survey technique. It was analyzed for each platoon upto 420m at every 30 m interval. The analyses revealed the trend and dispersion of platoons of vehicles and locations where initial platoon diffusion and higher platoon diffusion occur at downstream of traffic signals.